In The Pursuit of The Perfect Thyroid Care - Manas Kumar Sahoo; Nahim Barron (Journal of Thyroid Cancer, 2018)
A clinical perspective on optimizing thyroid care spans diagnostics, surgical indications, and long‑term follow‑up, aiming to align practice with patient goals and evidence.
Keywords: Thyroid